Swellable synthetic layered silicate lump and swellable synthetic layered silicate powder
The rapid cooling method during the production of swellable synthetic layered silicates significantly reduces cristobalite impurities, addressing the challenge of high impurity levels and increasing product purity.
Patent Information
- Application Number
- JP2021106511
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-28
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-06-28
AI Technical Summary
Existing methods for producing swellable synthetic layered silicates often result in high levels of cristobalite impurities, which are difficult to remove and increase production costs.
A method involving a heating step where a mixture of raw materials is heated to melt and then cooled rapidly at a rate of 100°C/min or higher to 900°C, producing a swellable layered silicate mineral mass with reduced cristobalite content.
This method effectively reduces the amount of cristobalite impurities in swellable synthetic layered silicates, resulting in a higher purity product with fewer adverse effects.
Smart Images

Figure 0007654484000008 
Figure 0007654484000009 
Figure 0007654484000010
Abstract
Description
[Technical field]
[0001] The present disclosure relates to lumps of swellable synthetic layered silicates. The present disclosure relates to powders including powders of swellable synthetic layered silicates. The present disclosure also relates to methods for producing layered silicates. [Background technology]
[0002] A melt synthesis method is known as a method for producing layered silicates (see, for example, Patent Document 1). In the melt synthesis method, raw materials mixed according to the chemical composition of the layered silicate are heated and melted, and the resulting melt is cooled to produce a crystallized layered silicate. In the production method described in Patent Document 1, the raw materials are melted within 20 minutes, and the melt is cooled at a cooling rate of 0.01°C / min to 50°C / min.
[0003] Patent Document 2 describes a method for producing synthetic hectorite, in which a smectite-type clay mineral containing cristobalite is treated with alkali under conditions in which the crystal structure of the cristobalite is substantially lost. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 4216510 [Patent Document 2] Japanese Unexamined Patent Publication No. 62-59518 Summary of the Invention [Problem to be solved by the invention]
[0005] According to a general melt synthesis method, cristobalite is generated as an impurity. In the method described in Patent Document 1, the raw material is rapidly melted to reduce the amount of cristobalite impurities in the lump of swellable synthetic layered silicate. However, even with the method described in Patent Document 1, 3 volume % (about 2.6 mass %) of cristobalite is still contained in the lump of swellable synthetic layered silicate, and it is expected that cristobalite can be further reduced.
[0006] The swellable synthetic layered silicate is usually powdered by crushing the ore. Therefore, the removal of cristobalite by classification after crushing is also considered. However, it is difficult to reduce the amount of cristobalite by classification, and the loss of the swellable synthetic layered silicate is also large.
[0007] In the method described in Patent Document 2, the viscosity is reduced by alkali treatment. soil Cristobalite in the mineral is treated. However, it is difficult to reduce the amount of cristobalite in the swellable synthetic layered silicate even by the alkali treatment described in Patent Document 2. In addition, increasing the number of steps such as the alkali treatment leads to an increase in the production cost of the swellable synthetic layered silicate.
[0008] Therefore, there is a demand for lump and powder of swellable synthetic layered silicate with reduced amount of cristobalite impurity, and a demand for a simple method for producing layered silicate with reduced amount of cristobalite impurity. [Means for solving the problem]
[0009] According to a first aspect of the present disclosure, Sodium tetrasilicic mica Contains a swellable synthetic layered silicate, The average crystallite size of the swellable synthetic layered silicate determined from the X-ray diffraction peak of the (060) plane is 14 nm to 18 nm, and calculated by the method shown below. A swellable synthetic layered silicate nugget is provided having a cristobalite content of less than 1% by weight. [Method for measuring cristobalite content] 0.800±0.001g of powdered ore and 0.200±0.001g of alumina as an internal standard were weighed and mixed. The mixed sample was measured using an X-ray diffractometer. The integrated intensity I 1 (cps) and the integrated intensity I of the alumina peak near 2θ=25.6°2 The cristobalite content X in the ore mass is calculated using the following formula: X(mass%)=(I 1 / I 2 ) / a=I 1 / (I 2 ×a) In the formula, a represents the slope of the calibration curve, which is 0.0462.
[0010] According to a second aspect of the present disclosure, The present invention relates to a pulverized ore mass of the swellable synthetic layered silicate. A powder of swellable synthetic layered silicate is provided. Powder Average particle size but 5μm~30μm. Wet synthetic layered silicate Powder For 1 part by mass, cristobalite is 2 x 10 -3 parts by mass or less.
[0011] According to a third aspect of the present disclosure, there is provided a method for producing an expandable layered silicate, comprising: a heating step of heating and melting a mixture of raw materials for synthesizing an expandable layered silicate; and a cooling step of cooling the molten material produced in the heating step to at least 900°C at a cooling rate of 100°C / min or more to produce a lump of the expandable layered silicate. Effect of the Invention
[0012] The amount of cristobalite, which is an impurity, contained in the lump of swellable synthetic layered silicate of the present disclosure is small. The lump of swellable synthetic layered silicate of the present disclosure can provide a powder of swellable synthetic layered silicate with few impurities.
[0013] The powder of the present disclosure contains a small amount of cristobalite, which is an impurity, and the powder of the present disclosure can reduce the adverse effects caused by cristobalite.
[0014] According to the method for producing a layered silicate of the present disclosure, the amount of cristobalite, which is a by-product contained in a swellable synthetic layered silicate, can be reduced in a simple manner. [Brief description of the drawings]
[0015] [Figure 1] X-ray diffraction patterns of the products in Test Examples 1 and 4. [Diagram 2] A partially enlarged view of the X-ray diffraction pattern in Figure 1. [Diagram 3] A partially enlarged view of the X-ray diffraction pattern in Figure 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Preferred embodiments of each of the above aspects are described below.
[0017] According to a preferred embodiment of the first aspect, the swellable synthetic layered silicate has an average crystallite size of 14 nm to 18 nm as determined from the X-ray diffraction peak of the (060) plane.
[0018] According to a preferred embodiment of the first aspect, the swellable synthetic layered silicate is sodium tetrasilicic mica.
[0019] According to a preferred embodiment of the first aspect, each lump weighs 10 g or more.
[0020] According to a preferred embodiment of the second aspect, the swellable synthetic layered silicate has an average crystallite size of 14 nm to 18 nm as determined from the X-ray diffraction peak of the (060) plane.
[0021] According to a preferred embodiment of the second aspect, the powder is in the form of a slurry dispersed in an aqueous medium.
[0022] According to a preferred embodiment of the second aspect, the swellable synthetic layered silicate is sodium tetrasilicic mica.
[0023] According to a preferred embodiment of the third aspect, the content of cristobalite in the lump is 1 mass % or less with respect to the mass of the lump.
[0024] According to a preferred embodiment of the third aspect, the method for producing a swellable layered silicate further comprises a grinding step of wet or dry grinding the lump to produce a powder of the layered silicate.
[0025] According to a preferred embodiment of the third aspect, the swellable layered silicate is sodium tetrasilicic mica.
[0026] According to a preferred embodiment of the third aspect, the method for producing an expandable layered silicate does not include a removal step for removing cristobalite contained in the lump.
[0027] In the following description, the reference numerals in the drawings are added for the purpose of understanding the invention, and are not intended to limit the invention to the illustrated embodiments. The drawings are intended to aid in the understanding of the lump and powder of swellable synthetic layered silicate and the manufacturing method thereof of the present disclosure, and are not intended to limit the lump and powder of swellable synthetic layered silicate and the manufacturing method thereof to the form of the drawings, such as the illustrated shape, size, scale, etc. In each embodiment, the same elements are given the same numerals.
[0028] In the present disclosure, the term "lump" refers to a lump of swellable synthetic layered silicate produced by cooling a melt obtained by melting the raw materials of the swellable synthetic layered silicate. The lump also includes a lump in a state before being crushed into powder. The lump is not limited to a solid lump after the production of the swellable synthetic layered silicate. The lump also includes a lump obtained by dividing or crushing a lump after production into smaller lump. The size of the lump depends on the production scale of the layered silicate and the subsequent processing. The lump can be, for example, 10 grams or more, 100 grams or more, 1 kilogram or more, 10 kilograms or more, 50 kilograms or more, or 100 kilograms or more. The lump can be 200 kilograms or less, 100 kilograms or less, 50 kilograms or less, 10 kilograms or less, 1 kilograms or less, 100 grams ...50 grams or less. The shape of the lump depends on the shape of the molten body when it is cooled, the shape after division and crushing, etc.
[0029] In the present disclosure, swellable refers to the ability to expand (increase in volume) when it absorbs water. Unless otherwise specified, in the present disclosure, swellable synthetic layered silicate refers to a synthetic layered silicate in a dry state, i.e., a synthetic layered silicate in a non-swollen state.
[0030] The swellable layered silicate of the present disclosure can be represented by the following formula: X 1 / 3~1 Y 2~3 Z 4 O 10 F 2 In the above formula, the elements which can be substituted at the X, Y and Z positions are shown in the form of ions as follows: X:Na + , Li + , K + , Ca 2+ , Sr 2+ , B.A. 2+ ; Y:Mg 2+ , Li + , Ni 2+ , B 3+ , Co 3+ , Zn 2+ , Mn 3+ , Al 3+ , Cr 3+ , Fe 2+ , Fe 3+ ; Z:Al 3+ , Si 4+ , Ge 4+ , B 3+ , Fe 3+ , Ti 4+ .
[0031] Examples of layered silicates include swellable mica. Examples of mica include sodium tetrasilicic mica (NaMg 2.5 (Si 4 O 10 )F 2 ) can be mentioned.
[0032] A lump of swellable synthetic layered silicate according to the first embodiment of the present disclosure will now be described.
[0033] The ore mass comprises a swellable synthetic layered silicate. The content of the swellable synthetic layered silicate can be 99% or more, 99.5% or more, or 99.9% or more by weight based on the weight of the ore mass. If no impurities are detected, the ore mass can be considered to be substantially 100% by weight of the swellable synthetic layered silicate.
[0034] The amount of cristobalite in the lump is preferably less than 1% by mass, more preferably 0.5% by mass or less, and even more preferably 0.1% by mass or less, based on the mass of the lump. The amount of cristobalite in the lump is even more preferably below the detection limit in quantitative analysis based on X-ray diffraction. Cristobalite is a by-product in the production of swellable synthetic layered silicate.
[0035] The cristobalite content in a lump can be measured, for example, by quantitative analysis using an internal standard method based on X-ray diffraction. In the internal standard method, a calibration curve is created to show the correlation between the integrated intensity of the X-ray diffraction peak of cristobalite and an internal standard sample (e.g., alumina) in order to quantify cristobalite. The calibration curve is created by measuring X-ray diffraction patterns for multiple mixtures of cristobalite and the internal standard sample with different amounts of cristobalite, and plotting the integrated intensity I of the cristobalite-derived peak against the amount X of cristobalite. 1 / Integrated intensity of peak derived from internal standard sample I 2 The slope a can be calculated from the calibration curve. A specified amount of the internal standard sample is added to the measurement sample to quantify cristobalite, and the sample is mixed and the X-ray diffraction pattern is measured. The integral intensity I of the specified cristobalite peak is calculated. 1 (For example, the integral intensity of the peak (Miller index (hkl): 102) at 2θ = 31.4°) and the integral intensity I 2 (For example, in the case of alumina, the integrated intensity of the peak (Miller index (hkl): 012) near 2θ=25.5° is read. The cristobalite content X (mass%) can be calculated using the following formula. X(mass%)=(I 1 / I 2) / a=I 1 / (I 2 ×a)
[0036] The average crystallite size of the swellable synthetic layered silicate is preferably 14 nm or more. The average crystallite size is preferably 18 nm or less. When the swellable synthetic layered silicate is synthetic mica, the crystallite size can be calculated from the following formula based on the X-ray diffraction peak of the (060) plane. The average crystallite size can be the average value of three measurements. D = Kλ / (Bcosθ) D: crystallite size (nm), K: Scherrer constant, λ: wavelength of X-rays (nm), B: broadening of diffraction line width (full width at half maximum (FWHM)) (radian), θ: Bragg angle (radian)
[0037] The content of impurities, particularly cristobalite, contained in the lump of swellable synthetic layered silicate according to the first embodiment of the present disclosure is very low, less than 1 mass %, so that a powder of swellable synthetic layered silicate with few impurities, i.e., the powder according to the second embodiment, can be obtained simply by crushing the lump.
[0038] A powder according to a second embodiment of the present disclosure will now be described.
[0039] The powder includes a powder of swellable synthetic layered silicate. The powder of swellable synthetic layered silicate can be obtained by pulverizing the lump of the first embodiment. The particle shape of the powder can be, for example, a plate shape, a flake shape, a scale shape, or the like.
[0040] The average particle size of the particles (including the swellable synthetic layered silicate) in the powder is not particularly limited. The powder can have an average particle size according to the purpose. As the average particle size, the median particle size (median value of particle size) can be adopted. For example, the median particle size of the powder can be 0.1 μm or more, 1 μm or more, 2 μm or more, 5 μm or more, 7 μm or more, or 10 μm or more. In addition, the median particle size can be 200 μm or less, 100 μm or less, 50 μm or less, 40 μm or less, 30 μm or less, 20 μm or less, 10 μm or less, or 5 μm or less. The median particle size can be measured, for example, by laser diffraction particle size distribution measurement.
[0041] The average thickness of the particles in the powder (including the swellable synthetic layered silicate) can be, for example, 1 nm or more, 5 nm or more, 10 nm or more, 50 nm or more, 0.1 μm or more, and 0.3 μm or more. The average thickness of the particles in the powder can be, for example, 1 μm or less, 0.5 μm or less, 0.3 μm or less, 0.2 μm or less, 0.1 μm or less, or 80 nm or less. The method for measuring the average thickness is not particularly limited, but for example, the thickness of any number of particles can be measured by tilt observation with an electron microscope, and the average thickness can be calculated.
[0042] The average aspect ratio (median particle size / average thickness) of the particles (including swellable synthetic layered silicate) in the powder can be, for example, 20 or more, 50 or more, 70 or more, 100 or more, 200 or more, 300 or more, 400 or more, or 500 or more. The upper limit of the average aspect ratio of the particles in the powder is not particularly limited, and is preferably 10,000 or less from the viewpoint of viscosity. The average aspect ratio of the particles in the powder can be, for example, 5,000 or less, 4,000 or less, 3,000 or less, 2,000 or less, 1,000 or less, 500 or less, 400 or less, 300 or less, 200 or less, 150 or less, 100 or less, or 80 or less. The method for determining the average aspect ratio is not particularly limited, but for example, the particle size and thickness of any number of particles determined by tilt observation with an electron microscope are measured, and the obtained median particle size value is divided by the average thickness value to calculate.
[0043] The crystallite size of the swellable synthetic layered silicate in the powder can be the same as in embodiment 1. It is believed that the smaller crystallite size allows the particles to be thinner.
[0044] The content of the swellable synthetic layered silicate powder in the powder can be 1% by mass or more, 5% by mass or more, 10% by mass or more, 20% by mass or more, 30% by mass or more, 40% by mass or more, 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 99% by mass or more, 99.5% by mass or more, or 99.9% by mass or more, based on the mass of the powder. In addition, when other powders and impurities are not detected in the powder, the content of the swellable synthetic layered silicate in the powder can be considered to be 100% by mass. The method for quantifying the swellable synthetic layered silicate in the powder can be appropriately selected depending on the other powders contained. For example, an internal standard method based on X-ray diffraction is an option. In addition, when the swellable synthetic layered silicate contains fluorine, a fluorine component analysis is an option.
[0045] In the powder of the present disclosure, cristobalite is 2×10 -3 Less than parts by mass , good Preferably 1.5 x 10 -3 parts by mass or less, more preferably 1×10 -3 Parts by mass or less, moreover Preferably 5 x 10 -4 Parts by mass or less, especially Preferably 1 x 10 -4 It is preferable that the amount of cristobalite is less than the detection limit. The amount of cristobalite in the powder can be measured by quantitative analysis using the internal standard method based on X-ray diffraction described above.
[0046] Powders of the present disclosure can also include powders other than swellable synthetic layered silicates.
[0047] The powder of the present disclosure may be in the form of a dry powder. The powder of the present disclosure may also be in the form of a slurry (suspension) dispersed in a dispersion medium. For example, water, lower alcohols such as ethanol, and mixtures thereof may be used as the dispersion medium. The content of the powder (dry state) in the slurry may be, for example, 0.1% by mass or more, 3% by mass or more, or 10% by mass or more relative to the mass of the slurry. The content of the powder in the slurry may be, for example, 50% by mass or less, 30% by mass or less, or 15% by mass or less relative to the mass of the slurry.
[0048] In the powder of the present disclosure, the relative amount of cristobalite to the swellable synthetic layered silicate is low. This can reduce the adverse effects of cristobalite. For example, when the powder of the present disclosure is a synthetic mica powder, applying the powder of the present disclosure to a skin topical agent can reduce the foreign body sensation caused by cristobalite, and the user can obtain a smoother feel when using the agent, compared to applying a synthetic mica powder containing about 2 to 10% cristobalite. In addition, when the powder of the present disclosure is applied to the skin, it can be made to adhere more closely to the skin and not easily come off. Furthermore, when the powder of the present disclosure is applied to a gas barrier film, the cristobalite can be effectively absorbed into the skin. about 2 The barrier performance can be improved compared to when synthetic mica powder containing up to 10% is used.
[0049] A method for producing a layered silicate according to a third embodiment of the present disclosure will be described.
[0050] The manufacturing method according to the present disclosure includes a heating step of melting a raw material for a layered silicate, and a cooling step of cooling the melt melted in the heating step.
[0051] As the raw material for the layered silicate, a material used in the conventional internal heat melting method can be used. For example, raw materials containing the constituent elements of the above-mentioned swellable synthetic layered silicate may be mixed and used according to the desired chemical composition. For example, when the swellable layered silicate is sodium tetrasilicic mica (NaMg 2.5(Si 4 O 10 )F 2 ) as the raw material, SiO 2 , MgO and Na 2 SiF 6 A mixture of these in a molar ratio of 3.15-3.85:2.25-2.75:0.45-0.55 can be used. Natural minerals such as feldspar, olivine, and talc can also be used as the Si, Al, and Mg sources. When replacing X, Y, and Z with other elements, the mixture of the compounds exemplified above can be mixed with oxides, fluorides, carbonates, and the like of the elements to be replaced and melted.
[0052] As the melting furnace for melting the raw materials, for example, a general internally heated melting furnace, an externally heated melting furnace, a high-frequency induction heating furnace, etc. can be used. Among them, a high-frequency induction heating furnace is preferably used. When an internally heated melting furnace or a high-frequency induction heating furnace is used, the heating time required for melting can be adjusted to be short by reducing the actual amount of raw materials charged from the standard amount. In addition, in the case of an externally heated melting furnace, instead of charging the blended raw materials into the furnace at room temperature, the inside of the furnace is heated in advance, and the raw materials are charged when the temperature inside the furnace reaches 1200°C or higher, thereby adjusting the heating time required for melting to be short.
[0053] The heating temperature for melting the raw materials is 1200°C to 1800°C, preferably 1400°C to 1600°C.
[0054] In the cooling step, the melt is quenched at a cooling rate of 100°C / min or more, preferably 150°C / min or more, more preferably 200°C / min or more. Quenching is preferably performed in a temperature range from the molten state to at least 900°C. The temperature range below 900°C may be allowed to cool naturally. If the quenching rate is 100°C / min or more, the amount of cristobalite produced as a by-product can be reduced. The temperature in the cooling step is the outer surface temperature (radiation temperature) of the melt.
[0055] The method for quenching the molten body is not particularly limited, and any method may be used. For example, a method in which the molten body is taken out of the furnace and then quenched in a mold provided with a water-cooling jacket, a method in which the molten body is quenched in a cooling bed, etc. may be applied. The mold may be cooled by either water cooling or air cooling. The cooling bed may have a structure provided with a cooling jacket.
[0056] This makes it possible to obtain the swellable synthetic layered silicate according to the first embodiment. The content of cristobalite in the lump obtained by the cooling step can be the content in the lump shown above.
[0057] The method for producing a layered silicate according to the third embodiment may further include a grinding step in which at least a part of the lump obtained in the cooling step is ground to produce a layered silicate powder. The grinding method is not particularly limited and may be any method. For example, first, the lump of the swellable layered silicate is coarsely ground by a general crusher such as a jaw crusher or a hammer crusher. After this, the coarsely ground raw material is powdered by a dry grinder such as a hammer mill, a roll mill, or a Raymond mill to produce a layered silicate powder. The grinding method may be a wet method or a dry method. The grinding can be performed so that the powder has a desired average particle size. The powder according to the second embodiment can be produced by the grinding step. The content of cristobalite in the powder obtained by the grinding step can be the content in the powder shown above.
[0058] When the pulverization is performed in a wet method, the pulverization can be performed in an aqueous medium. As the aqueous medium, for example, water, alcohols including ethanol, etc. can be used. After the pulverization, a slurry (suspension) in which the swellable synthetic layered silicate is dispersed can be obtained.
[0059] The powder obtained by the grinding step is dispersed in an aqueous medium to obtain a slurry in which the powder of the swellable synthetic layered silicate is dispersed.
[0060] The method for producing a layered silicate according to the third embodiment does not need to include a removal step of removing cristobalite. Examples of the removal step include a method of removing cristobalite by classifying powder, a method of removing cristobalite by heating a lump or powder, and a method of removing cristobalite by treating powder with alkali. This can reduce the number of steps.
[0061] When the ore and powder produced without using the manufacturing method of the present disclosure contain 5% by mass or more of the by-product cristobalite, it is difficult to reduce the cristobalite content to 1% by mass or less even with the removal method described above.
[0062] According to the method for producing a layered silicate according to the third embodiment, it is possible to produce a lump of the swellable synthetic layered silicate according to the first embodiment, and a powder according to the second embodiment.
[0063] According to the method for producing a layered silicate according to the third embodiment, it is possible to suppress the production of cristobalite, which is a by-product during the synthesis of a layered silicate, thereby producing a layered silicate with high purity.
[0064] The layered silicate masses and powders of the present disclosure may be difficult or simply impractical to directly identify by their composition, structure, identity, etc. In such cases, the layered silicate masses and powders of the present disclosure should be allowed to be identified by their method of manufacture. EXAMPLES
[0065] The layered silicate lump, powder, and method for producing the layered silicate of the present disclosure will be described below with examples. However, the layered silicate lump, powder, and method for producing the layered silicate are not limited to the following examples.
[0066] [Test Example 1] Silicon dioxide 51.9 k g, magnesium oxide 24.9 kg, and sodium silicofluoride 23.2 k 100g of molten raw material k g was heated to 1450°C in an internally heated melting furnace using carbon electrodes and held for 10 minutes to melt the raw material mixture. The melt was removed from the furnace and placed in an iron mold equipped with a water-cooling jacket, and quenched to 900°C at a cooling rate of 203°C / min. It was then cooled to room temperature and crystallized to obtain a lump of sodium tetrasilicic mica, a swellable synthetic layered silicate. The cristobalite content of the obtained lump was measured.
[0067] [Test Example 2] Except for the cooling rate, the ore lump was prepared in the same manner as in Test Example 1. In Test Example 2, the melt was quenched at a cooling rate of 115° C. / min. The cristobalite content of the obtained ore lump was measured.
[0068] [Test Example 3] Except for the cooling method, the ore lump was prepared in the same manner as in Test Example 1. In Test Example 3, the melt was poured into a cooling bed equipped with a water-cooling jacket and quenched at a cooling rate of 321°C / min. The cristobalite content of the obtained ore lump was measured.
[0069] [Test Example 4] The chemical composition of sodium tetrasilicic mica is based on 100% molten raw material. k g was heated to 1450°C in an internally heated melting furnace using carbon electrodes and held for 10 minutes to melt the raw material mixture. The melt was removed from the furnace, placed in an iron mold, and cooled to 900°C at a cooling rate of 36°C / min. It was then cooled to room temperature and crystallized to obtain an ore lump. The cristobalite content of the ore lump obtained was measured.
[0070] [Measurement of cristobalite content] The amount of cristobalite produced in each test example was measured by an internal standard method based on X-ray diffraction. Alumina was used as the internal standard substance. A calibration curve was created in advance to identify the amount of cristobalite produced. X-ray diffraction patterns were measured for a mixture of 20 mass% alumina, cristobalite and calcium fluoride (remainder, dilution material) with the cristobalite ratio changed to 1 mass%, 10 mass%, 25 mass%, and 50 mass%. For each X-ray diffraction chart, the integrated intensity I 2 and the integrated intensity I of the cristobalite peak (Miller index (hkl): 102) at 2θ = 31.4° 1 The integral intensity I of the cristobalite peak was then read against the cristobalite content. 1 / integrated intensity of alumina peak I 2 A calibration curve was created by plotting the above. The slope a of the created calibration curve was measured. The slope a of the created calibration curve was 0.0462.
[0071] Next, the X-ray diffraction patterns of the ore lump obtained in each test example were measured. First, the ore lump obtained in each test example was powdered and dried. Next, 0.800±0.001 g of the powder of each test example and 0.200±0.001 g of alumina as an internal standard were weighed and mixed. The X-ray diffraction patterns of the mixed samples were measured using an X-ray diffractometer (MiniFlex600-C (Rigaku Corporation)) with Cu-Kα radiation. In each X-ray diffraction chart, the integrated intensity I 1 (cps) and the integrated intensity I of the alumina peak (Miller index (hkl): 012) at 2θ = 25.6° 2(cps) was read. The cristobalite content X contained in the synthetic mica produced in each test example was calculated from the following formula. Table 1 shows the measurement results of the cristobalite content. In Table 1, "less than 0.1" indicates that the cristobalite content was below the detection limit because no significant peak of cristobalite could be detected, i.e., the integrated intensity of the cristobalite peak was zero.
[0072] X(mass%)=(I 1 / I 2 ) / 0.0462=I 1 / (I 2 ×0.0462)
[0073] Fig. 1 shows a comparison diagram of the X-ray diffraction patterns of the products in Test Example 1 and Test Example 4. Fig. 2 shows an enlarged view of the cristobalite peak in the X-ray diffraction pattern shown in Fig. 1. Fig. 3 shows an enlarged view of the alumina (internal standard) peak in the X-ray diffraction pattern shown in Fig. 1.
[0074] [Table 1]
[0075] As shown in Figures 1 and 2 ,cold In Test Examples 1 to 3, in which the cooling rate was 100°C / min or more, no cristobalite was detected in the X-ray diffraction pattern. On the other hand, in Test Example 4, in which the cooling rate was 36°C / min, 9.6 mass% of cristobalite was detected in the lump. Cooling rate It was found that the formation of the by-product cristobalite could be suppressed by setting the rate at 100°C / min or more.
[0076] [Test Example 5] 5 g of the sodium tetrasilicic mica lump prepared in Test Example 1 was added to 100 ml of ion-exchanged water and stirred for 12 hours, after which it was classified using a centrifuge to obtain a slurry with an average particle size of 10 μm. The slurry had sufficient viscosity and was suitable as a coating material.
[0077] Even when the lump was pulverized to change it into a powder form, the cristobalite content in the powder and the amount of cristobalite per part by mass of synthetic mica were the same as those in Test Examples 1 to 4.
[0078] [Test Example 6: Measurement of crystallite size] The crystallite size was measured for the synthetic micas produced in Test Examples 1 to 4. The crystallite size was calculated from the following formula by measuring the half-width of the peak at about 2θ=61° derived from the (060) plane by X-ray diffraction. CuKα rays were used as X-rays, and λ=0.154 nm. K was 0.89. The crystallite size was the average value of three X-ray diffraction measurements. The measurement results are shown in Table 2.
[0079] D = Kλ / (Bcosθ) D: crystallite size (nm), K: Scherrer constant, λ: wavelength of X-rays (nm), B: half-width (rad), θ: Bragg angle (rad)
[0080] [Table 2]
[0081] The synthetic mica powders of Test Examples 6-1 to 6-3 produced in Test Examples 1 to 3 had smaller crystallite sizes than the synthetic mica powder of Test Example 6-4 produced in Test Example 4. It is believed that the synthetic mica of Test Examples 6-1 to 6-3 had smaller crystallites because they were crystallized by rapid cooling. It is believed that the smaller crystallite size allows the particles of the swellable synthetic layered silicate to be made thinner.
[0082] [Test Example 7: Friction test] The effect of the content of cristobalite in the swellable synthetic layered silicate on the frictional sensation when the swellable synthetic layered silicate is applied was tested. In the friction test, the mean coefficient of friction (MIU) and the mean deviation of the coefficient of friction (MMD) were measured. MIU represents the slipperiness felt by the applicator when applying the swellable synthetic layered silicate powder. The smaller the MIU value, the more slipperiness the applicator feels. The MIU value is preferably less than 0.8. MMD represents the smoothness and roughness felt by the applicator when applying the swellable synthetic layered silicate powder. The smaller the MMD value, the more smooth the applicator feels.
[0083] For the friction test, the synthetic mica lump produced in Test Example 1, which had a cristobalite content below the detection limit (less than 0.1% by mass), and the synthetic mica lump produced in Test Example 4, which contained 9.6% by mass of cristobalite, were each pulverized by a Raymond mill. The lump in Test Examples 1 and 4 was pulverized to the same degree by the same method. The powders in Test Examples 7-1 and 7-3 were from the same lot. The powders in Test Examples 7-2 and 7-4 were from the same lot. For the friction test, a friction tester KES-KS (manufactured by Kato Tech Co., Ltd.) using a silicon sensor was used. The test was performed by applying 0.01 g of powder evenly onto artificial leather. The powder in each test example was measured three times, and the average value was calculated. The measurement results for MIU are shown in Table 3. The measurement results for MMD are shown in Table 4. The measurement conditions are as follows; SENS:H Frictional static load: 25gf Measurement distance: 20mm Measurement speed: 1mm / sec Sensor: 10mm square sensor Temperature: 20.5℃±2℃ Humidity: 60%±2℃
[0084] [Table 3]
[0085] [Table 4]
[0086] The MIU of Test Examples 7-1 and 7-2 was less than 0.8, and both powders were slippery. The powder of Test Example 7-3 was smoother and less rough than Test Example 7-4. The particle shape of synthetic mica was flat (scaly), while the particle shape of cristobalite was other than flat. Therefore, the powder obtained from Test Example 1 was free of foreign matter, and was therefore smoother and less rough. This demonstrated that the powder of the present disclosure is suitable for application to the skin.
[0087] In addition, the powder of Test Example 7-3 had a smaller MMD value, which means that when the powder is applied to a coating, it has less unevenness and is easier to align uniformly and densely. From this, it was found that the powder of the present disclosure is also suitable for improving gas barrier properties, as shown in Test Example 8 below.
[0088] [Test Example 8: Gas Barrier Test] The gas barrier performance (water vapor permeability) was tested for films coated with the synthetic mica powder produced in Test Example 1, which had a cristobalite content below the detection limit (less than 0.1 mass%), and the synthetic mica powder produced in Test Example 4, which contained 9.6 mass% cristobalite.
[0089] The gas barrier test was carried out in accordance with the cup method (JIS Z0208). For the gas barrier test, the ore lump produced in Test Example 1 and the ore lump produced in Test Example 4 were each pulverized in a Raymond mill and used as powder. The ore lump in Test Examples 1 and 4 was pulverized to the same extent by the same method.
[0090] The synthetic mica powder of each test example was dispersed in water to prepare a slurry. A polyurethane water-soluble resin (Takelac (registered trademark) WPB-341 (Mitsui Chemicals MC Co., Ltd.)) was added to this slurry so that the total mass of the powder and the water-soluble resin was 15% by mass relative to the mass of the slurry, and mixed to prepare a coating liquid. Coating liquids with different contents of synthetic mica powder in the coating liquid, namely, no addition (0% by mass), 10% by mass, and 20% by mass relative to the total mass of the water-soluble resin and the powder, were prepared. Next, the coating liquid was applied to a polyethylene terephthalate film (PET film) with a thickness of 12 μm so that the thickness before drying was 10 μm, and dried in a dryer. The test cup with the obtained film attached and containing 7 g of calcium chloride as a moisture absorbent was left for 24 hours in a constant temperature and humidity chamber adjusted to a temperature of 40° C. and a humidity of 90% RH. The water vapor transmission rate (WVTR) was calculated from the following formula. The water vapor transmission rate was calculated from the following formula. Table 5 shows the measurement results (g / (m 2 Indicates the day.
[0091] WVTR(g / (m 2 ·day)) = (mass of test cup after water vapor exposure (g) - mass of test cup before water vapor exposure (g)) / film area (m 2 )
[0092] [Table 5]
[0093] The higher the water vapor transmission rate value shown in Table 5, the lower the gas barrier performance of the film. Films coated with synthetic mica with a low amount of cristobalite had higher gas barrier performance than films coated with synthetic mica with a high amount of cristobalite. It is believed that the gas barrier performance was improved by reducing the gap between the powder and the PET film when there was less cristobalite, an impurity. It is also believed that the gas barrier performance was improved because the powder particles were thinner.
[0094] [Test Example 9: Cristobalite removal test by alkali treatment] The synthetic mica powder produced in the above-mentioned Test Example 4 was subjected to alkali treatment to remove cristobalite. Synthetic mica powder containing 9.6% by mass of cristobalite was produced from the lump produced in Test Example 4, and the powder was dispersed in water to make a slurry of 5% by mass. Sodium hydroxide, sodium carbonate, or magnesium hydroxide was added to the slurry in the amounts shown in Table 6, and the slurry was heated at 95°C to 98°C for 5 hours. After the heat treatment, the treated product was dried and pulverized into powder. The content of cristobalite was measured by an internal standard method based on X-ray diffraction. The alkali treatment conditions and the amount of remaining cristobalite are shown in Table 6. Test Examples 9-2 to 9-4 were obtained by alkali treatment of synthetic mica of the same production lot as Test Example 9-1. The reduction rate shown in Table 6 is the change rate relative to the content of cristobalite in Test Example 9-1.
[0095] [Table 6]
[0096] In both alkali treatments, most of the cristobalite remained. It was found that it is difficult to reduce the cristobalite content to 1 mass% or less using alkali treatment.
[0097] [Test Example 10: Cristobalite removal test by heat treatment] An attempt was made to remove cristobalite by heat treatment of synthetic mica powder made from the lump made in the above Test Example 4. 20 g of powder was heat treated at 450°C, 650°C, and 850°C, respectively. The heat treatment conditions, and the content and rate of change of cristobalite are shown in Table 7. Test Examples 10-2 to 10-4 were made by heat treating synthetic mica of the same production lot as Test Example 10-1. The rate of change shown in Table 7 is the rate of change relative to the content of cristobalite in Test Example 10-1.
[0098] [Table 7]
[0099] When the powder was heat-treated, the amount of cristobalite tended to decrease. However, most of the cristobalite remained in all heat treatments. It was found that it is difficult to reduce the cristobalite content to 1 mass% or less by heat treatment.
[0100] [Test Example 11: Cristobalite removal test by classification] The synthetic mica powder produced in the above Test Example 4 was subjected to a classification process to remove cristobalite. The classification process was carried out by dispersing the swellable synthetic layered silicate in water and then centrifuging it. Compared to before classification, the synthetic mica was reduced by about 30% by mass, but the content of cristobalite did not change. Therefore, it was found that it is difficult to remove cristobalite by classification.
[0101] The swellable synthetic layered silicate, powder and the method for producing the same of the present invention have been described based on the above-mentioned embodiments and examples, but are not limited to the above-mentioned embodiments and examples, and may include various modifications, changes and improvements to each of the disclosed elements (including elements described in the claims, specification and drawings) within the scope of the present invention and based on the basic technical idea of the present invention. Furthermore, various combinations, substitutions or selections of each of the disclosed elements are possible within the scope of the claims of the present invention.
[0102] Further objects, objectives and modes (including modifications) of the present invention will become apparent from the entire disclosure of the present invention including the claims.
[0103] With respect to numerical ranges set forth herein, unless otherwise stated, any numerical value or range falling within that range should be construed as being specifically set forth herein. [Industrial Applicability]
[0104] The swellable synthetic layered silicate, powder, mixed powder, and their manufacturing methods of the present disclosure can be applied to, for example, cosmetics, paints, metal ion adsorbents, films, nanocomposite materials, gas barrier improving materials for paper, films, paints, and other materials, viscosity adjusting materials for inks, paints, and cosmetics, modifiers for resins and the like, flame retardant materials, chemical resistant materials, ion adsorbents, gasket materials, lubricants, conductive materials, laser marking materials, thermal recording materials, dispersants, drawing materials, dispersants, and the like.
Claims
1. A swellable synthetic layered silicate that is sodium tetrasilicic mica, The average crystallite size of the swellable synthetic layered silicate determined from the X-ray diffraction peak of the (060) plane is 14 nm to 18 nm; A lump of swellable synthetic layered silicate having a cristobalite content of less than 1 mass% as determined by the method described below. [Method for measuring cristobalite content] 0.800±0.001 g of the ore powder and 0.200±0.001 g of alumina as an internal standard substance are weighed out and mixed together. The mixed sample is measured using an X-ray diffractometer. In the X-ray diffraction chart, the integrated intensity I1 (cps) of the cristobalite peak near 2θ=31.4° and the integrated intensity I2 (cps) of the alumina peak near 2θ=25.6° are read, and the cristobalite content X in the ore is calculated using the following formula. X (mass%)=(I 1 / I 2 ) / a=I 1 / (I 2 ×a) In the formula, a is the slope of the calibration curve, which is 0.0462.
2. 2. The lump according to claim 1, wherein the average crystallite size of the swellable synthetic layered silicate determined from the (060) plane X-ray diffraction peak is 15.4 nm to 17.1 nm.
3. A lump of swellable synthetic layered silicate described in claim 1 or 2, wherein the cristobalite content is 0.1 mass% or less.
4. The ore lump according to any one of claims 1 to 3, wherein each lump weighs 10 g or more.
5. A powder of swellable synthetic layered silicate which is a pulverized product of a lump of the swellable synthetic layered silicate according to any one of claims 1 to 4, The powder of the swellable synthetic layered silicate has an average particle size of 5 μm to 30 μm; The amount of cristobalite is 2×10 per 1 part by mass of the wettable synthetic layered silicate powder. -3 parts by weight or less of a powder of swellable synthetic layered silicate.
6. The powder according to claim 5, wherein the average crystallite size of the swellable synthetic layered silicate determined from the X-ray diffraction peak of the (060) plane is 14 nm to 18 nm.
7. 7. The powder according to claim 5 or 6, wherein the powder is in the form of a slurry dispersed in an aqueous medium.
8. 8. The powder according to claim 5, wherein the swellable synthetic layered silicate is sodium tetrasilicic mica.
9. A powder described in any one of claims 5 to 8, in which cristobalite has not been removed from the ground material.
Citation Information
Patent Citations
Composition having both conductive property and ion exchange property and preparation thereof
JP1982030553A
Production of synthetic hectorite
JP1987059518A
Production of fluoromica
JP1998053408A
Swellable synthetic fluorine mnica
JP1999199224A
Swelling synthetic fluorine mica-based mineral and gas barrier layered body using the same
JP2004331460A